Co-simulation study of performance trade-offs between centralised, distributed, and hybrid adaptive PEV charging algorithms - Mansour, Samah; Harrabi, Intissar; Maier, Martin; Joós, Géza (Computer networks (Amsterdam, Netherlands : 1999), 2015)
In this paper, we propose a decentralised algorithm for coordinating the charging of multiple plug-in electric vehicles (PEVs) and extend it to a hybrid version by including the PEV’s charging strategies into the optimisation function. Going one step further, we also consider coordinated workplace charging integrating PV panels. The main focus of our work is to conduct a comparative study between a centralised benchmark algorithm, and the proposed decentralised and hybrid approaches from both communications and power perspectives. All algorithms are co-simulated over a converged fiber-wireless communication infrastructure of 342 residential customers. Power system results prove the efficiency of the proposed algorithms providing up to 19% peak shaving while meeting drivers’ requirements. Communication results of the decentralised algorithm compared to a centralised benchmark scheme provided better performance, measuring an upstream traffic rate of 1.28 Mbps with a maximum delay of 0.629 ms. Compared to the decentralised algorithm, the hybrid algorithm showed a promising improvement for large fleets of PEVs accompanied with an overhead communication cost that is significantly less than that of the centralised algorithm.